2022
DOI: 10.1155/2022/5652172
|View full text |Cite
|
Sign up to set email alerts
|

Wenyang Huazhuo Tuihuang Formula Inhibits the Th17/Treg Cell Imbalance and Protects against Acute-on-Chronic Liver Failure

Abstract: Objective. Acute-on-chronic liver failure (ACLF) is a group of chronic liver diseases and caused by acute internal and external liver injury. Wenyang Huazhuo Tuihuang (WYHZTH) formula had a good clinical effect on promoting the resolution of jaundice. The aim of this study is to further investigate the mechanism of the WYHZTH formula in the ACLF rat model. Methods. The ACLF rat model was constructed by combining human serum albumin with LPS and D-gal. WYHZTH was used to intervene and treat. The cytokines IL-17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The administration of D-Gal/LPS in mice induced liver necrosis and inflammation similar to human hepatitis (203,204). Previous studies demonstrated that coadministration of LPS at doses of 10-100 µg/kg and D-Gal at doses of 100-1000 mg/kg was performed to establish an acute liver failure mouse model (205)(206)(207)(208)(209).…”
Section: Carbon Tetrachloride-induced Druginduced Liver Injury Modelmentioning
confidence: 99%
“…The administration of D-Gal/LPS in mice induced liver necrosis and inflammation similar to human hepatitis (203,204). Previous studies demonstrated that coadministration of LPS at doses of 10-100 µg/kg and D-Gal at doses of 100-1000 mg/kg was performed to establish an acute liver failure mouse model (205)(206)(207)(208)(209).…”
Section: Carbon Tetrachloride-induced Druginduced Liver Injury Modelmentioning
confidence: 99%